Molecular Mechanism of Naringenin Against High-Glucose-Induced Vascular Smooth Muscle Cells Proliferation and Migration Based on Network Pharmacology and Transcriptomic Analyses - He, Wenjun; Wang, Yanming; Yang, Rui; Ma, Huihui; Qin, Xuqing; Yan, Meijuan; Rong, Yi; Xie, Yufang; Li, Li; Si, Junqiang; Li, Xinzhi; Ma, Ketao (Frontiers in Pharmacology, 2022)
Although the protective effects of naringenin (Nar) on vascular smooth muscle cells (VSMCs) have been confirmed, whether it has anti-proliferation and anti-migration effects in high-glucose-induced VSMCs has remained unclear. This study aimed to clarify the potential targets and molecular mechanism of Nar when used to treat high-glucose-induced vasculopathy based on transcriptomics, network pharmacology, molecular docking, and in vivo and in vitro assays. We found that Nar has visible anti-proliferation and anti-migration effects both in vitro (high-glucose-induced VSMC proliferation and migration model) and in vivo (type 1 diabetes mouse model). Based on the results of network pharmacology and molecular docking, vascular endothelial growth factor A (VEGFA), the proto-oncogene tyrosine-protein kinase Src (Src) and the kinase insert domain receptor (KDR) are the core targets of Nar when used to treat diabetic angiopathies, according to the degree value and the docking score of the three core genes. Interestingly, not only the Biological Process (BP), Molecular Function (MF), and KEGG enrichment results from network pharmacology analysis but also transcriptomics showed that phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) is the most likely downstream pathway involved in the protective effects of Nar on VSMCs. Notably, according to the differentially expressed genes (DEGs) in the transcriptomic analysis, we found that cAMP-responsive element binding protein 5 (CREB5) is a downstream protein of the PI3K/Akt pathway that participates in VSMCs proliferation and migration. Furthermore, the results of molecular experiments in vitro were consistent with the bioinformatic analysis. Nar significantly inhibited the protein expression of the core targets (VEGFA, Src and KDR) and downregulated the PI3K/Akt/CREB5 pathway. Our results indicated that Nar exerted anti-proliferation and anti-migration effects on high-glucose-induced VSMCs through decreasing expression of the target proteins VEGFA, and then downregulating the PI3K/Akt/CREB5 pathway, suggesting its potential for treating diabetic angiopathies.